A methodology to select the electric propulsion system for Platform Supply Vessels (PSV). - Morales Vásquez, Cristian Andrés (2014)
The present work proposes a methodology to define the electric propulsion system for PSVs. This methodology was applied to a case study: the conceptual design of a PSV for operation at the pre-salt fields at Santos basin. First, four different alternatives of electric propulsion systems for the PSV are presented and sized. The first one has induction motors as main propulsion motors, the second one has synchronous motors as main propulsion motors; the third and fourth alternatives are the same as the first and second, respectively, with a batteries bank connected to the main switchboard. Each of the four arrangements was contemplated with two options for Diesel generators: high speed and medium speed generator sets. The mass, volume, fuel consumption, exhaust gases emissions and reference capital costs for each arrangement are estimated and analyzed. Moreover, an economic analysis through the Net Present Value (NPV) is performed. The methodology ends with the Analytic Hierarchy Process (AHP) to support the decision making procedure. Some of the parameters obtained for each arrangement (mass, volume, fuel consumption, exhaust gases and NPV) are used as criteria and sub-criteria for selection. Two scenarios are evaluated, the first scenario gives more importance to the financial component of the design; the second scenario sets the exhaust gases emissions as the more significant parameter. The results were different, the arrangements 1 and 2 with medium speed Diesel generator sets appear as the most suitable option from the economical point of view; whereas the arrangements with batteries and high speed Diesel gensets are the best options to reduce the exhaust emissions.